Development of student attendance using fingerprint identification method / Nadiah Saari … [et al.] - Saari, Nadiah; Baharom, Bahardin; Ismail, Fauzilah; Abu Bakar, Azinoor Azida; Ibrahim, Norisham (Division of Research and Industry Linkages, 2017)
The development of an attendance management system using biometrics has been widely recognised in the current decade. Biometric system refers to the automated recognition of individuals based on their biological and behavioural characteristics such as fingerprint, face, iris and voice. The easy-to-use, efficient and reliable system makes biometrics more preferable than the other forms or methods of recording attendance. Every academic institution has certain criteria for students regarding their attendance in class, and therefore, keeping the accurate record of attendance is very important. At present, attendance is usually noted using paper sheets and the old file system and instructors have to regularly update the record and manually calculate the percentage of classes attended. Not only this method is taxing, especially when one has more than one group or class of students, but it also allows for impersonation and the attendance sheet could be lost or stolen. In this study, the development of student attendance system using fingerprint identification method has been done to replace the manual system of using attendance sheet. Student credentials were stored in the database linked to a fingerprint device and the attendance records were copied to a spreadsheet designed to suit the guideline and requirements as specified by the Department of Academic and International Affairs (HEA), UiTM. Using the fingerprint identification method, the process of recording student attendance is simpler, paperless and more secure as this system eliminates student impersonation and loss of attendance sheet records. In addition, the developed spreadsheet serves as an aid to instructors in finding absentees through the attendance history effortlessly, and thus, a proper action can be taken at an early stage to prevent truancy. A readily maintain record-keeping that saves time, cost, energy and institution resources is accomplished from this study.